2017
DOI: 10.1139/apnm-2016-0525
|View full text |Cite
|
Sign up to set email alerts
|

Minimal muscle damage after a marathon and no influence of beetroot juice on inflammation and recovery

Abstract: DisclaimerThe University of Gloucestershire has obtained warranties from all depositors as to their title in the material deposited and as to their right to deposit such material.The University of Gloucestershire makes no representation or warranties of commercial utility, title, or fitness for a particular purpose or any other warranty, express or implied in respect of any material deposited.The University of Gloucestershire makes no representation that the use of the materials will not infringe any patent, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
109
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(119 citation statements)
references
References 55 publications
(93 reference statements)
7
109
1
2
Order By: Relevance
“…A summary of their physical characteristics and training history is displayed in Table 1. Samples were obtained from a sub-group of participants taking part in a larger study (Clifford et al 2016); only those whose samples were collected before mid-day were included to limit diurnal variation. The participants completed a health-screening questionnaire to assess the eligibility for the study and were excluded if they had any cardiovascular complications, a recent (<3 months) musculoskeletal injury or were receiving prescribed anti-inflammatory medications other than for asthma.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A summary of their physical characteristics and training history is displayed in Table 1. Samples were obtained from a sub-group of participants taking part in a larger study (Clifford et al 2016); only those whose samples were collected before mid-day were included to limit diurnal variation. The participants completed a health-screening questionnaire to assess the eligibility for the study and were excluded if they had any cardiovascular complications, a recent (<3 months) musculoskeletal injury or were receiving prescribed anti-inflammatory medications other than for asthma.…”
Section: Methodsmentioning
confidence: 99%
“…Of the female participants still menstruating, the marathon took place during the early/mid luteal phase. The environmental conditions on the day of the race have been described before (Clifford et al 2016). Briefly, at the start of the race air temperature was 3.8 °C; humidity 82%; barometric pressure 1013 hpa and wind speed 9 km/h; the weather remained dry throughout and the temp increased to 8.1 °C towards the end of the race.…”
Section: Methodsmentioning
confidence: 99%
“…Some emerging evidence suggests that beetroot juice may support aspects of exercise recovery by mitigating loss of muscle function [126] and soreness [126, 127] after certain types of exercise [127]. However, not all studies have demonstrated a benefit with beetroot juice ingestion on mitigating soreness or exercise-induced inflammation post-exercise [128]. …”
Section: Micronutrientsmentioning
confidence: 99%
“…Most reported effects of beetroot supplements were focused on its effect over muscle injury. Those results obtained were supporting antioxidant and anti-inflammatory mechanisms that includes several biomarkers such as, CPK, ALT, AST, CRP, interleukin-6 (IL-6), interleukin-8 (IL-8), tumor necrosis factor-α (TNFα), and others 31 . Further studies reported a potential beneficial positive effect of using beetroot juice in a carbon tetrachloride induced oxidative stress in an animal study.…”
Section: Introductionmentioning
confidence: 57%